Integração das tecnologias da indústria 4.0 com o lean manufacturing - Martins, Tailise Mascarenhas (2023)
The research aims to analyze the impact of the interaction between Industry 4.0 technologies and the Lean Manufacturing concept on organizational operational performance, from the perspective of manufacturing managers, considering relevant information from a systematic literature review. The objective of integrating LM and I4.0 is to understand how LM impacts operational performance through systematic and continuous pursuit of waste reduction and improvement by interacting with I4.0 technologies, which introduce automation and interconnectivity and can mitigate pre-existing management difficulties. The study is based on a systematic literature review conducted in the SCOPUS and Web of Science databases, covering 54 articles, and on subsequent multiple case studies. The review identified 15 Lean Manufacturing tools, 18 I4.0 technologies, and 12 most cited improvements/benefits to date, which served as the basis for the case questionnaire and analyses of the multiple case studies. Multiple case studies were conducted in three manufacturing companies, using questionnaires, data collection from company websites, and interviews to triangulate data. The aim was to identify the interaction of I4.0 technologies with Lean Manufacturing tools and understand the maturity trajectory of I4.0 in each company. The results indicate that Lean Manufacturing is the foundation for successful implementation of Industry 4.0. This integration provides benefits such as increased confidence in data, productivity, and operational performance. The study offers managerial implications, highlighting how Lean tools can eliminate waste and effectively collaborate with the introduction of I4.0 technologies. Lessons learned from the case study companies provide valuable insights for improving the overall performance of companies integrating these tools and technologies.